Medidas Comportamentais de Eficácia: Contribuições na Avaliação do Ensino de Operações Aritméticas - Henklain, Marcelo Henrique Oliveira; Carmo, João Dos Santos; Lopes Júnior, Jair (Instituto de Psicologia, Universidade de Brasília, 2016)
Abstract We investigated measures of efficiency (ratio of correct responses and resolution time) and error (distance between emitted response and the correct response) in a group of Elementary School students. Experiment 1 comprised pre-test, teaching of equivalence between different forms of problem presentation, post-test 1, teaching of addition algorithm, post-test 2, teaching of subtraction algorithm, post-test 3, and generalization test. Experiment 2 was similar to Experiment 1 until post-test 1, followed by training of scale problem-solving, post-test 2, generalization test 1, teaching of addition and subtraction algorithms, post-test 3, and generalization test 2. The results of this study suggest that measuring efficiency and error contribute to evaluate the effectiveness of educational programs in teaching problem solving.

Resumo Investigaram-se medidas de eficiência (razão entre acertos e tempo de solução) e erro (diferença entre a resposta emitida e a resposta correta) com estudantes do Ensino Fundamental. O Experimento 1 compreendeu pré-teste, ensino de equivalência entre diferentes formas de apresentação de problemas, pós-teste 1, ensino do algoritmo de adição, pós-teste 2, ensino do algoritmo de subtração, pós-teste 3 e teste de generalização. O Experimento 2 foi semelhante ao anterior até o pós-teste 1, seguido de treino de solução de problemas na forma de balança, pós-teste 2, teste de generalização 1, ensino dos algoritmos de adição e subtração, pós-teste e teste de generalização 2. Medir eficiência e erro contribui para a avaliação da eficácia de programas de ensino de solução de problemas.
Behavioral Measures of Efficacy: Contributions to the Evaluation of Arithmetical Operations Teaching
Keywords: educational program evaluation; problem solving; mathematics education; avaliação de programa educacional; solução de problemas; ensino da matemática